Avaliação do potencial tóxico reprodutivo do extrato de Cordia ecalyculata Vell: em ratos Wistar - Santos, Mirian Campos [UNESP] (2014)
The use of extracts from Cordia ecalyculata is growing due to their potential to inhibit appetite. Its side effects on reproduction are unknown. Then , the study evaluated the reproductive toxic potential of different doses of the extract of C. ecalyculata in adult rats. The animals (n = 12/group) received distilled water (control group) and the hydroethano lic extract of C. ecalyculata in different doses (20, 100 and 400 mg / kg body weight). Treatments were administered orally (gavage), single dose/day for 60 consecutive days. At the end of treatment, the body weight of the animals that received the extract was similar to the control group, demonstrating the ineffectiveness of this herbal medicine in reducing body weight. The weight of the testes, seminal glands and prostate were no affected by treatments (p>0.05), but increased there was (p < 0.05) on the epididymis weight at a dose of 400 mg / kg of the extract. At all doses, the testes and epididymides showed histopathological changes, increased (p <0.05) the percentage of abnormal gametes in the epididymal tail and fertility of anim als was reduced (p<0.0 5). In conclusion that the extract of Cordia ecalyculata promoted re productive toxicity, but without dose - dependent effect